Ever Directed Towards the Lord: The Love of God in the Liturgy of the Eucharist Past, Present, and Hoped For - Lang, Uwe Michael (Bloomsbury Publishing Plc, 2007)
The celebration of the liturgy of the Holy Eucharist is one of the central issues in the Roman Catholic Church today. To mark the "Year of the Eucharist", the Society of St. Catherine of Siena held a conference on the Eucharistic liturgy at Oxford in 2005. This book contains theÃÂ energetic and fruitful reflection of the scholars present at the conference. The contributions are academically demanding yet accessible to a wider audience.ÃÂ The collectionÃÂ does not seekÃÂ a solution to the current problems,ÃÂ rather itÃÂ promotes an open discussion about the theological, philosophical and historical issues surrounding theÃÂ celebration of the liturgy and its future as well as paying attention to the increasing interest in the pre-conciliar rites.